STUDY OF THE TITLES OF FEATURE FILMS AND TV SERIES IN ENGLISH AND UZBEK: STRUCTURAL-SEMANTIC AND LINGUODIDACTIC ASPECTS - Azzamova Charosxon Alisher qizi; Shaxnoza Fayziyeva Xayrullayevna (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Annotation: This study explores the structural-semantic and linguodidactic aspects of feature film and TV series titles in English and Uzbek. It aims to analyze how these titles convey meaning and their educational implications for language learners.